Ethnicity and Inequality in China, de Björn A. Gustafsson, Reza Hasmath y Sai Ding - Aguilar Romero, María Paula M. (México y la Cuenca del Pacífico, 2023)
Gustafsson, B. A., Hasmath, R., & Ding, S. (2021). Ethnicity and Inequality in China. Routledge, 356 pp.